Pulmonary Aspergillosis in Critically Ill COVID-19 Patients Admitted to the Intensive Care Unit: A Retrospective Cohort Study - Felix Bergmann; Anselm Jorda; Amelie Blaschke; Cornelia Gabler; Serhii Bohdan; Alina Nussbaumer-Pröll; Christine Radtke; Markus Zeitlinger (Journal of Fungi, 2023)
COVID-19-associated pulmonary aspergillosis (CAPA) is a life-threatening fungal infection that mainly affects critically ill patients. The aim of this study was to assess the incidence and clinical outcomes of putative CAPA in critically ill COVID-19 patients. This retrospective observational cohort study included 181 cases from 5 ICUs at Vienna General Hospital between January 2020 and April 2022. Patients were diagnosed with putative CAPA according to the AspICU classification, which included a positive Aspergillus culture in a bronchoalveolar lavage sample, compatible signs and symptoms, and abnormal medical imaging. The primary outcome was adjusted 60-day all-cause mortality from ICU admission in patients with vs. without putative CAPA. Secondary outcomes included time from ICU admission to CAPA diagnosis and pathogen prevalence and distribution. Putative CAPA was identified in 35 (19.3%) of 181 COVID-19 patients. The mean time to diagnosis was 9 days. Death at 60 days occurred in 18 of 35 (51.4%) patients with CAPA and in 43 of 146 (29.5%) patients without CAPA (adjusted HR (95%CI) = 2.15 (1.20–3.86, p = 0.002). The most frequently isolated Aspergillus species was Aspergillus fumigatus. The prevalence of putative pulmonary aspergillosis in critically ill COVID-19 patients was high and was associated with significantly higher mortality.